CATASTROPHIC GAS HYDRATE GROWTH UNDER SHUT-IN AND COLD START UP CONDITIONS - SUNDRAMOORTHY, JEGA DIVAN (2015)
In this present work, capillary aided catastrophic gas hydrate growth is observed under shut-in and cold start-up conditions employing newly fabricated customized apparatus, consisting of six units of identical rocking gas hydrate cell. The observation of a capillary-aided mass-transport mechanism for a catastrophic hydrate growth with and without kinetic hydrate inhibitor is presented. Visual observation shows that the hydrate crystal formation at the brine wetted area close to the brine/gas interface initiates capillary-aided catastrophic hydrate growth. Moreover, no masstransfer restriction of brine towards catastrophic gas hydrate growth is observed. The capillary force may provide a greater driving force to form gas hydrates than the diffusion rate of gasses into the bulk water phase. It is also found that the production profiles such as different shut-in time and capillary aided water transport influences the produce water to grow hydrate in distinctive ways.